Lack of association between the serotonin transporter and serotonin 1A receptor: an in vivo PET imaging study in healthy adults. (30th September 2016) - Strupp-Levitsky, Michael; Miller, Jeffrey M.; Rubin-Falcone, Harry; Zanderigo, Francesca; Milak, Matthew S.; Sullivan, Gregory; Ogden, R. Todd; Oquendo, Maria A.; DeLorenzo, Christine; Simpson, Norman; Parsey, Ramin V.; Mann, J. John
Abstract: The serotonin neurotransmitter system is modulated in part by the uptake of syn aptically released serotonin (5-HT) by the serotonin transporter (5-HTT), and by specific serotonin autoreceptors such as the somatodendritic 5-HT1A receptor, which can limit serotonin neuron depolarization. However, little is known about how 5-HTT and 5-HT1A are related in vivo . To study this question, we reanalyzed positron emission tomography (PET) data obtained earlier in 40 healthy participants (21 females) using [ 11 C]WAY-100635 for quantification of 5-HT1A binding and [ 11 C](+)-McN-5652 for quantification of 5-HTT binding. We hypothesized negative correlations between 5-HT1A binding in the raphe nuclei (RN) and 5-HTT binding in RN terminal field regions. Controlling for sex, no significant correlations were found (all p>0.05). Similarly, an exploratory analysis correlating whole-brain voxel-wise 5-HTT binding with 5-HT1A binding in RN identified no significant clusters meeting our a priori statistical threshold. The lack of correlation between 5-HT1A and 5-HTT binding observed in the current study may be due to the different temporal responsiveness of regulatory processes controlling the somatodendritic 5-HT1A receptor and 5-HTT in response to changing availability of intrasynaptic serotonin. Highlights: Brain serotonin transporter (5-HTT) and serotonin 1A receptor were quantified via PET. Serotonin 1A receptor and 5-HTT binding are not correlated in a priori regions. This suggests different regulatory control for these proteins in the serotonin system.